2004
DOI: 10.1158/1078-0432.ccr-03-0071
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Randomized Trial of Autologous Formalin-Fixed Tumor Vaccine for Postsurgical Recurrence of Hepatocellular Carcinoma

Abstract: Purpose: We conducted a Phase II clinical trial with randomized patients to determine whether autologous formalin-fixed tumor vaccine (AFTV) protects against postsurgical recurrence of hepatocellular carcinoma (HCC).Experimental Design: Forty-one patients with HCC who had undergone curative resection were randomly allocated to the vaccine treatment (n ‫؍‬ 19) or no adjuvant control group (n ‫؍‬ 22). Three intradermal vaccinations were administered at 2-week intervals beginning 4 -6 weeks after hepatic resectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
75
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 93 publications
(81 citation statements)
references
References 30 publications
1
75
0
3
Order By: Relevance
“…© 2006 American Association for Cancer clincancerres.aacrjournals.org Downloaded from colony-stimulating factor, IL-2, and Bacillus Calmette-Guerin (24). Forty-one stage I-IIIa subjects, postcurative resection, were enrolled and randomized; 19 received vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…© 2006 American Association for Cancer clincancerres.aacrjournals.org Downloaded from colony-stimulating factor, IL-2, and Bacillus Calmette-Guerin (24). Forty-one stage I-IIIa subjects, postcurative resection, were enrolled and randomized; 19 received vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…developed an autologous formalin-fixed tumor vaccine (AFTV) for in vivo induction of killer lymphocytes, 5,16 suppression of recurrence of hepatocellular carcinoma after primary resection, 12 and treatment of recurrent GBM in a pilot clinical trial. 6 Our previous prospective clinical trial for preliminary evaluation of the efficacy of AFTV concomitant with fractionated radiotherapy (FRT), but not with concomitant TMZ, in patients with newly diagnosed GBM (study identification no.…”
mentioning
confidence: 99%
“…Over the past decade, a number of clinical trials have been conducted to examine the potential for the activation of tumour-specific T cells in HCC patients, many have shown biological activity and a subset has shown antitumour efficacy (Iwashita et al, 2003;Butterfield, 2004;Kuang et al, 2004). Recent reports on clinical trial of AFP-based vaccine indicated that spontaneous AFP-specific immunologic responses had been induced in vaccinated HCC patients.…”
mentioning
confidence: 99%